The role of soluble CD40L in autoimmune diseases - Meryem Mabrouk; Hicham Wahnou; Yahye Merhi; Haissam Abou-Saleh; Fadila Guessous; Younes Zaid (Journal of Translational Autoimmunity)
CD40−CD40L is essential for immune system modulation because it coordinates both adaptive and inflammatory responses.Systemic lupus erythematosus, multiple sclerosis, inflammatory bowel disease, thrombocytopenic purpura, and rheumatoid arthritis are among the autoimmune illnesses in which it is especially prominent. Thus, the CD40−CD40L axis is a significant therapeutic target, despite the fact that its inhibition was first constrained by thromboembolic adverse effects.New therapeutic approaches, such as nanotechnological methods and new-generation monoclonal antibodies, have been developed as a result of recent research with the goal of enhancing therapy efficacy and safety. This study opens up new avenues for the treatment of autoimmune illnesses by examining the pathophysiological consequences of CD40−CD40L and reviewing new treatments that target this pathway.